The Calculation of the Ettingshausen Coefficient in Quantum Wells under the Influence of Confined Phonons (for Electron – confined Optical Phonon Scattering) - Nguyen, Thi Lam Quynh (H. : ĐHQGHN, 2019)
In this paper, we have used the method of quantum kinetic equation to calculate the analytic expression for Ettingshausen coefficient (EC) under the influence of confined phonon. We considered a quantum well in the presence of constant electric field, magnetic field and electromagnetic wave (EMW) with assumption that electron – confined optical phonon (OP) scattering is essential. The EC obtained depends on many quantities in a complicated way such as temperature, magnetic field, frequency or amplitude of EMW and m - quantum number which specify confined OP. Numerical results for GaAs/GaAsAl quantum well (QW) have displayed clearly the differences in comparison with both cases of bulk semiconductor and unconfined phonon. The result of examining the EC’s dependence on magnetic field shows that quantum number m changes resonance condition; m not only makes the increase in the number of resonance peak but also changes the position of peaks. When m is set to zero, we get the results that corresponds to unconfined OP.